DC optimizer-based decentralized frequency support scheme of large-scale PV plants considering partial shading conditions. (November 2022) - Wang, Qin; Fang, Jiakun; Yao, Wei; Li, Dahu; Ai, Xiaomeng; Wen, Jinyu
Abstract: Solar energy loss of the large-scale PV power plant (LPVPP) caused by partial shading can be mitigated by unit-level DC optimizers (DCO). This paper presents a novel DCO-based decentralized control (DBDC) scheme for an LPVPP to provide active frequency support without equipping energy storage. The proposed DBDC scheme consists of two levels: the plant-level modified DC-link voltage control for the PV inverter and the unit-level improved virtual inertia control and lookup table-based droop control deployed in the DCO controller for each PV generation unit. The stored energy of the DC-link capacitor can be adjusted for inertia emulation based on grid frequency fluctuation with plant-level voltage control. Meanwhile, the frequency deviation is converted into the changes of DCO output voltages. Then, according to the voltage deviations of DCOs, the adaptive power adjustment for PV units is realized through unit-level virtual inertia and droop control scheme. Finally, the maximum use of the PV reserve power and the proposed DBDC scheme without using any communication network can be achieved for LPVPPs, even under frequent partial shading conditions. Case studies are undertaken on a PV-integrated two-area system. Comparison simulation results verify the effectiveness and universality of the proposed DBDC scheme under different scenarios. Graphical abstract: Highlights: DCO-based frequency support scheme is proposed for large-scale PV systems. Communication-free decentralized inertia and droop controls are employed in DCOs. High solar energy utilization for PV arrays even under partial shading conditions. Superior frequency regulation effect compared with conventional methods.